PERAN PANGKALAN UDARA PANGERAN M. BUN YAMIN BANDAR LAMPUNG DALAM PENANGGULANGAN BENCANA GUNA MENDUKUNG KEAMANAN NASIONAL - Yanuar Udianto Kurniadi; Dina Subagia; Fadhiil Ali Hakim; Bayu Anggi Nugraha; Rohmat Hidayat; Syamsul Maarif (Universitas Muhammadiyah Tapanuli Selatan, 2020)
This study aims to determine the role of the Indonesian Air Force, especially the Pangeran M. Bun Yamin Air Base, located in Lampung Province in disaster management. So far, it is known that in disaster emergency response conditions, not only the BNPB and BPBD, SAR, and related agencies have taken to the field, but there is also a role for the TNI in it. The method used in this research is literature study where the data presented is the result of data collection that researchers have collected from journals and related references. As for the results found in the field, namely Pangeran M. Bun Yamin Air Base in its capacity to cope with disasters, not only decreased during the emergency response status, but also in the pre-disaster period, and also in the post-disaster period. The coordination carried out by Pangeran M. Bun Yamin Air Base in the case of disasters is coordination by Korem 043 / Garuda Hitam in the field of training and division of roles in disaster management so that there is no overlap or prevent sectoral egos in disaster management. Pangeran M. Bun Yamin Air Base has advantages in the air sector, namely being able to quickly help with logistics distribution by arranging the distribution of aid that cannot be reached by land routes, and also monitoring the affected conditions by air.